Dark Energy Survey Year 1 results: the lensing imprint of cosmic voids on the cosmic microwave background. Issue 1 (22nd October 2020) - Vielzeuf, P; Kovács, A; Demirbozan, U; Fosalba, P; Baxter, E; Hamaus, N; Huterer, D; Miquel, R; Nadathur, S; Pollina, G; Sánchez, C; Whiteway, L; et al.
ABSTRACT: Cosmic voids gravitationally lens the cosmic microwave background (CMB) radiation, resulting in a distinct imprint on degree scales. We use the simulated CMB lensing convergence map from the Marenostrum Institut de Ciencias de l'Espai (MICE) N -body simulation to calibrate our detection strategy for a given void definition and galaxy tracer density. We then identify cosmic voids in Dark Energy Survey (DES) Year 1 data and stack the Planck 2015 lensing convergence map on their locations, probing the consistency of simulated and observed void lensing signals. When fixing the shape of the stacked convergence profile to that calibrated from simulations, we find imprints at the 3 σ significance level for various analysis choices. The best measurement strategies based on the MICE calibration process yield S/N ≈ 4 for DES Y1, and the best-fitting amplitude recovered from the data is consistent with expectations from MICE ( A ≈ 1). Given these results as well as the agreement between them and N -body simulations, we conclude that the previously reported excess integrated Sachs–Wolfe (ISW) signal associated with cosmic voids in DES Y1 has no counterpart in the Planck CMB lensing map.